PENGARUH TENURE AUDIT, ROTASI AUDIT, DAN UKURAN KANTOR AKUNTAN PUBLIK TERHADAP KUALITAS AUDIT - Nattaya Azzahra (2022)
This research aims to examine the effect of Audit Tenure, Audit Rotation, and Public Accounting Firm Size on Audit Quality. The sample of this research consisted of 43 infrastructure companies that are listed on the Indonesia Stock Exchange in period 2017-2020 which were selected using purposive sampling technique. The total of sample are 168 data. The tool that used in this research is SPSS 25. The analysis technique used is logistic regression analysis with a significance level of 5%. The result showed that (1) Audit Tenure has a positive and significant effect on Audit Quality (2) Audit Rotation has a positive and significant effect on Audit Quality (3) Public Accounting Firm Size has no effect on Audit Quality.